2017
DOI: 10.1016/j.arabjc.2014.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of bifunctionalized PEO–PPO–PEO triblock copolymers with applications as dehydrating agents for heavy crude oil

Abstract: A series of a,x-diamines of polyoxyethylene-polyoxypropylene-polyoxyethylene (POE-POP-POE) triblock copolymer was synthesized and experimentally evaluated as dewatering agents for heavy crude oil. A quantitative structure-activity relationship (QSAR) study of the effect of the secondary amine structure over the yield of nucleophilic substitution reactions with a,x-ditosylate ester of PEO-PPO-PEO triblock copolymer was performed exclusively at the DFT level. Multiple linear regression (MLR) analysis including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Each acrylic homopolymer structure was built in HyperChem 8.0 software, in accordance with a procedure previously described . In every case, homopolymers were geometrically optimized in this software employing the RM1 method and the Polak–Ribiere algorithm with a gradient of 0.01 kcal Å –1 mol –1 , RMS = 1 × 10 –8 , and 32 767 iteration limits.…”
Section: Experimental and Computational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Each acrylic homopolymer structure was built in HyperChem 8.0 software, in accordance with a procedure previously described . In every case, homopolymers were geometrically optimized in this software employing the RM1 method and the Polak–Ribiere algorithm with a gradient of 0.01 kcal Å –1 mol –1 , RMS = 1 × 10 –8 , and 32 767 iteration limits.…”
Section: Experimental and Computational Proceduresmentioning
confidence: 99%
“…Theoretical Calculation of V and log P. Each acrylic homopolymer structure was built in HyperChem 8.0 software, in accordance with a procedure previously described. 32 In every case, homopolymers were geometrically optimized in this software employing the RM1 method and the Polak−Ribiere algorithm with a gradient of 0.01 kcal Å −1 mol −1 , RMS = 1 × 10 −8 , and 32 767 iteration limits. Once all structures were fully optimized, physicochemical parameters such as molecular volume (V) and partition coefficient (log P) were calculated from QSAR application, implemented in HyperChem software.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Almost all organic materials can be oxidized into CO 2 and H 2 O by hydroxyl radicals and peroxide ions . Thus, the copolymer template of P123 with HOMO (−0.3197 eV) and LUMO (0.0821 eV) levels that occur within the bandgap of WO 3 can be degraded by WO 3 as a photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…17 While bottle test is widely used in labs to evaluate the performance of different demulsifiers, quantitative structure− activity relationship (QSAR) analysis has become a powerful theoretical tool for description and prediction of the properties of complex molecules. However, its application in the oil industry has been limited to corrosion inhibitors, 18,19 additives, 20,21 and interfacial phenomena on emulsion stability, 22 and up to now, only few studies have reported the QSAR analysis of block bipolymers functionalized with secondary 23 and tertiary amines 24 for the dewatering of heavy crude oils.…”
Section: Introductionmentioning
confidence: 99%